Exploring the Effects of Mentorship on Technological Innovation Among Women in Andean Textile Communities - Miguel Angel Ortiz-Esparza; David Rondon; Klinge Villalba-Condori; Claudia Acra-Despradel; Briseida Sotelo-Castro (CLEI Electronic Journal)
This study focuses on evaluating the influence of mentoring in technological tools on women operating in the textile sector in the high Andean areas of Cusco, Puno, Tacna, Moquegua and Arequipa in southern Peru. To measure this impact, surveys were conducted before and after the virtual mentorships, focusing on the acquisition of basic level technology skills, such as Google search, use of Canva and social media management. The results indicate that the mentorships have influenced the development of technology skills among the participants. Pre-mentoring surveys revealed a generalized lack in most of these skills, with limited knowledge in the use of tools such as search engines and graphic design platforms. However, post- mentoring surveys showed improvements in these areas. This study highlights the importance of mentoring in the development of basic technological skills, empowering women in the textile sector in the high Andean regions. These results suggest that mentoring can play a key role in closing technology gaps and improving the active participation of this demographic group in the digital economy and society in general.